The role of Sarbanes-Oxley and ISO 9001 in corporate management a plan for integration of governance and operations - Stimson, William A. (McFarland & Co., 2012)
"This book's exploration of the relationship between corporate governance and operations uses the requirements of the Sarbanes-Oxley law as a guide and the internal controls of the ISO 9001 Quality Management System as the interface medium to unite the strategic and tactical functions of the corporation"--Provided by publisher.